Notes toward a performative theory of assembly - Butler, Judith (Harvard University Press, 2015)
Judith Butler elucidates the dynamics of public assembly under prevailing economic and political conditions, analyzing what they signify and how. Understanding assemblies as plural forms of perfomative action, Butler extends her theory of performativity to argue that precarity - the destruction of the conditions of livability - has been a galvanizing force and theme intoday's highly visible protests.
Keywords: approches et analyses; corps; discipline; genre; inégalités; militance; performativité; philosophie; précarité; ressource en ligne; sciences humaines; systèmes d'oppression; thématiques